PERANAN PEREMPUAN DALAM MASYARAKAT ISLAM DI ERA POST MODERNIASASI PENDEKATAN TAFSIR TEMATIK - Masturin, Masturin (AL-TAHRIR, 2015)
Abstract: The role of womenÂ  seems stillÂ  to be a discourse that becomes a debate among theÂ  feminist theoreticians. Something that becomes the crucial problem is how to position the role of women in contemporary Islamic societies. Through a thematic interpretation approach, this paper tried to describe the role of women in Islamic societies in the post-modern era. Discourse and gender movement had a great influence on Muslim society. The demands on the role of women were not only related to the role of freedom of their activities in the domestic realm but also related to the public domain. The Qur'an was present not in the empty time and but rather to respond to a variety of community activities in place in which it was revealed. He - the Quâ€™ran - had an idealistic normative values that should be believed, held and executed. The text data of the Quâ€™ran could be illustrated by a triadic system depicting the role of women and their relationships with the Lord, the roles and relationships of women in the family; and the roles and relationships in the community, including the Islamic community. Islam, as a religion, on the one hand was not only as a pure idea that was absolute and universal, but on the other hand, it was also as a product of the ideas that are not only relative but also limited. However, with its relativity and limitation as the product of the thought, it was still able to show the distinction of its egalitarian with the concept built by modern-secular feminism movement through the principle of parity.Ø§Ù„Ù…Ù„Ø®Øµ :Ø£ØµØ¨ØØª Ø§Ù„Ù…Ø±Ø£Ø© Ù…ÙˆØ¶ÙˆØ¹ Ù†Ù‚Ø§Ø´ Ø¨ÙŠÙ† Ù…ÙÙƒÙ‘Ø±Ø§Øª Ø§Ù„Ù†Ø³ÙˆÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„Ø¢Ù†. Ø§Ù„Ù‚Ø¶ÙŠØ© Ø§Ù„Ù…Ù‡Ù…Ù‘Ø© Ù‡ÙŠ ÙƒÙŠÙ ÙŠÙƒÙˆÙ† Ø¯ÙˆØ± Ø§Ù„Ù…Ø±Ø£Ø© ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø³Ù„Ù… Ø§Ù„Ù…Ø¹Ø§ØµØ±. ØØ§ÙˆÙ„Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© â€“ Ø¨Ù…Ø¯Ø®Ù„ Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹ÙŠ â€“ ØªØµÙˆÙŠØ± Ø¯ÙˆØ± Ø§Ù„Ù…Ø±Ø£Ø© ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø³Ù„Ù… ÙÙŠ Ø§Ù„Ø¹ØµØ± Ø¨Ø¹Ø¯ Ø§Ù„ØØ¯Ø§Ø«Ø©. Ø§Ù„ØØ±ÙƒØ© ÙˆØ§Ù„Ø£ÙÙƒØ§Ø±Â  Ø¹Ù† Ø§Ù„Ø¬Ù†Ø³ Ù„Ù‡Ø§ Ø£Ø«Ø±Ù‡Ø§ ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø³Ù„Ù…. Ø§Ù‚ØªØ¶Ø§Ø¡Ø§Øª Ø§Ù„Ù…Ø±Ø£Ø© Ù„ÙŠØ³ ÙÙ‚Ø· Ø¹Ù† ØØ±ÙŠÙ‘Ø© Ø§Ù„Ø¹Ù…Ù„ ÙÙŠ Ø§Ù„Ø£Ø³Ø±Ø© Ù„ÙƒÙ† ÙƒØ°Ù„Ùƒ ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹. ÙˆØ¥Ù† Ø§Ù„Ù‚Ø±Ø¢Ù† Ù„Ø§ÙŠÙ†Ø²Ù„ ÙÙŠ Ø«Ù‚Ø§ÙØ© Ù…Ø¬ØªÙ…Ø¹ ÙØ§Ø±ØºØ©ØŒ Ù„ÙƒÙ†Ù‘Ù‡ ÙŠØ³ØªØ¬ÙŠØ¨ Ø´ØªÙ‰ Ø§Ù„Ø£Ù†Ø´Ø·Ø© ÙˆØ§Ù„Ø£Ø¹Ù…Ø§Ù„ Ù‚Ø§Ù… Ø¨Ù‡Ø§ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ø°ÙŠ Ù†Ø²Ù„ ÙÙŠÙ‡. ÙˆØ§Ù„Ù‚Ø±Ø¢Ù† ÙÙŠÙ‡ ØªØ¹Ø§Ù„ÙŠÙ… ÙˆÙ‚ÙŠÙ… Ø£Ø¯Ø¨ÙŠØ© Ø´Ø§Ù…Ù„Ø© ÙƒØ§Ù…Ù„Ø© Ø§Ù„ØªÙŠ ÙŠØ¬Ø¨ Ø§Ù„Ø§Ø¹ØªÙ‚Ø§Ø¯ Ø¨Ù‡Ø§ ÙˆØ§Ù„ØªÙ…Ø³Ùƒ Ø¨Ù‡Ø§ ÙˆØ§Ù„Ø¹Ù…Ù„ Ø¨Ù‡Ø§. ÙˆØ§Ù„Ù†ØµÙˆØµ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© ØªÙ…Ø«Ù‘Ù„ ØªØ±ÙŠØ§Ø¯ÙŠÙƒ Ø§Ù„ØªÙŠ ØªØµÙˆÙ‘Ø± Ø¯ÙˆØ± Ø§Ù„Ù…Ø±Ø£Ø© ÙˆØ¹Ù„Ø§Ù‚ØªÙ‡Ø§ Ø¨Ø§Ù„Ù„Ù‡ØŒ Ø¯ÙˆØ±Ù‡Ø§ ÙˆØ¹Ù„Ø§Ù‚ØªÙ‡Ø§ Ø¨Ø§Ù„Ø£Ø³Ø±Ø©ØŒ ÙˆØ¯ÙˆØ±Ù‡Ø§ ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙˆØ®Ø§ØµØ© Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø³Ù„Ù…. ÙˆØ§Ù„Ø¥Ø³Ù„Ø§Ù… ÙƒÙƒÙˆÙ†Ù‡ Ø¢Ø±Ø§Ø¡ Ø£ØµÙŠÙ„Ø© ÙˆÙ‡Ùˆ Ø¹Ø§Ù… ÙˆÙ…Ø·Ù„Ù‚ØŒ Ù„ÙƒÙ† Ù„ÙƒÙˆÙ†Ù‡ Ù†ØªØ§Ø¦Ø¬ Ø£ÙÙƒØ§Ø± ÙÙ‡Ùˆ ØºÙŠØ± Ù…Ø·Ù„Ù‚ ÙˆÙ…ØØ¯Ù‘Ø¯. ÙˆÙ„ÙƒÙ† Ø¨ÙƒÙˆÙ†Ù‡ Ù…Ø«Ù„ Ù‡Ø°Ø§ØŒ Ø§Ø³ØªØ·Ø§Ø¹ Ø£Ù† ÙŠÙƒÙˆÙ† ÙØ§Ø±Ù‚Ø§ ÙˆØ§Ø¶ØØ§ Ø¨ÙŠÙ†Ù‡ ÙˆØ¨ÙŠÙ† Ø§Ù„Ù…ÙÙ‡ÙˆÙ…Ø§Øª Ø§Ù„ØªÙŠ Ø£ØªØª Ø¨Ù‡Ø§ Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù†Ø³ÙˆÙŠØ©Â  Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© Ø§Ù„Ø¹Ù„Ù…Ø§Ù†ÙŠØ© Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø§Ù„Ø£Ø³Ø§Ø³ Ø¨Ø§Ø±ØªØ§Ø³.Abstrak: Peran perempuan merupakan diskursus yang masih jadi perbincangan teoritisi feminis. Hal yang menjadi problem krusial adalah bagaimana memposisikan peran perempuan dalam masyarakat Islam kekinian. Melalui pendekatan tafsir tematik, tulisan ini mencoba untuk mendiskripsikan peran perempuan dalam masyarakat Islam di era post-modern. Wacana dan gerakan gender memiliki pengaruh besar bagi masyarakat Islam. Tuntutan peran tidak saja terkait kebebasan beraktifitas di ranah domestik tetapi juga terkait dengan ranah publik. Al-Qurâ€™an hadir tidak dalam ruang dan waktu yang hampa, melainkan merespon beragam aktifitas masyarakat di tempat ia diturunkan. Ia â€“ al-Qurâ€™an â€“ memiliki tata nilai normatif-idealitik yang harus diyakini, dipegang teguh dan dijalankan. Data-data teks al-Qurâ€™an, dapat diilustrasikan dengan sebuah triadik yang menggambarkan peran perempuan dan relasinya dengan Tuhan; peran dan relasi perempuan dalam keluarga; dan peran dan relasinya dalam masyarakat termasuk masyarakat Islam. Islam, sebagai sebuah agama, di satu sisi merupakan ide murni karenanya absolut dan universal, namun di sisi yang lain, ia merupakan hasil pemikiran yang tidak saja relatif tetapi juga terbatas. Namun dengan kerelatifan dan keterbatasan hasil pemikiran itu, ia tetap mampu menunjukkan distingsi egaliteriannya dengan konsepsi yang dibangun gerakan feminism modern-sekuler melalui prinsip paritas.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: tafsir, domestik, publik, absolut, sub-ordinat, paritas.